New Records for the Freshwater Algae of Turkey - Baykal, Tuelay; Akbulut, Aydin; Acikgoz, Ilkay; Udoh, Abel U.; Yildiz, Kazim; Sen, Buelet (Tubitak Scientific & Technological Research Council Turkey, 2009)
Algae samples were collected from important dam lakes and running waters of the Lower Euphrates Basin. Eighteen new records of Turkish freshwater algae were identified. Among these new records, 5 belong to Cyanophyta, 10 to Chlorophyta, 1 to Xanthophyta, and 2 to Bacillariophyta.
Keywords: Algae; new record; freshwater; South-East Anatolian region